FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN REMATIK PADA PENDERITA REMATIK DI KELURAHAN VI SUKU WILAYAH KERJA PUSKESMAS TANAH GARAM KOTA SOLOK - Afridon Afridon (Ensiklopedia Education Review, 2020)
Rheumatic disease is a disease affecting the joints and surrounding structures, consisting of more than 100 types. Rheumatoid Arthritis (RA) is a progressive autoimmune disease with chronic inflammation that attacks the musculoskeletal system but can involve the organs and systems of the body as a whole, characterized by swelling, joint pain and destruction of synovial tissue accompanied by movement disorders followed by premature death. This type of research is analytical, with a cross sectional design, where in this study, the dependent and independent variables will be observed at the same time, this method is expected to be known